Practising Student Voice in University Teaching and Learning : Three Anchoring Principles. - Cook-Sather, Alison; Matthews, Kelly (Journal of University Teaching & Learning Practice v.20 n.6 https://doi.org/10.53761/1.20.6.2, 2023)
In this invited commentary, we offer three principles to anchor understanding of student voice in university teaching and learning. Encompassing related concepts and practices, the principles we offer support a shift in (1) attitude toward, (2) structures for, and (3) goals of teaching and learning. In our introduction, we provide a short history of the concept of student voice and our reason for using the notion of anchoring to argue for embracing its practice. In the main body of our commentary, we share expanded reflections on what each of the three principles might look like in practice, grounded in examples and selected scholarship. We conclude with an invitation to continued dialogue about this work. [Author abstract]